Correlation Between Arabic Vocabulary Mastery and Arabic Speaking Ability - Suhadi, Muhammad; Fahrurozi (Academy of Education Journal, 2024)
In the era of globalization that continues to grow rapidly, mastery of foreign languages is one of the important skills needed in various aspects of life, both in the context of education, work, and social interaction, especially Arabic, but this is not accompanied by good vocabulary mastery to support speaking skills. Thus, the purpose of this study is to determine the correlation or relationship between Arabic vocabulary mastery and Arabic speaking skills. The research method used in this study is a quantitative research method with a population of approximately 75 students and a sample of 30 students. The results of this study indicate that there is a negative and significant relationship between Arabic Vocabulary Mastery and Arabic Speaking Skills with a sig. (2-tailed) value of 0.023, because the sig. (2-tailed) <0.05 means that there is a significant relationship between variable X and variable Y and the r value = 0.413 with a p value <0.05 that there is a correlation between the two variables, which means that the higher the Arabic Vocabulary Mastery, the lower the Arabic Speaking Skills. So it can be concluded that Arabic vocabulary mastery influences Arabic speaking ability.